2023
DOI: 10.1097/mpg.0000000000003705
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Anthropometry and Body Composition in Children With SARS-CoV-2-Associated Multisystem Inflammatory Syndrome

Abstract: Objectives: Acute coronavirus disease 2019 infection has been shown to negatively affect body composition among adult and malnourished or obesity children. Our aim is to longitudinally evaluate body composition in children affected by the Multisystem Inflammatory Syndrome (MIS-C). Methods: In this cohort study, we recruited 40 patients affected by MIS-C, aged 2–18 years old, who were admitted in our clinic between December 2020 and February 2021. Physical examination for each participant included weight, hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…В работе E. Di Profio с соавт. [12] приводятся результаты исследования состава тела в большой по численности популяции детей, перенесших острую форму COVID-19, а также обследованные спустя 6 месяцев после выздоровления. ИМТ и другие антропометрические параметры, связанные с жировым компонентом тела, были значительно выше через 6 месяцев после перенесенного заболевания.…”
Section: индекс массы тела и Covid-19unclassified
“…В работе E. Di Profio с соавт. [12] приводятся результаты исследования состава тела в большой по численности популяции детей, перенесших острую форму COVID-19, а также обследованные спустя 6 месяцев после выздоровления. ИМТ и другие антропометрические параметры, связанные с жировым компонентом тела, были значительно выше через 6 месяцев после перенесенного заболевания.…”
Section: индекс массы тела и Covid-19unclassified
“…Longitudinal studies revealed that COVID-19 infections may cause various types of malnutrition in children. 6 Although the negative effect of COVID-19 infection on nutritional status has been well defined in adults, the impact of malnutrition on the clinical course and outcomes of MIS-C is not clear in the pediatric population.…”
Section: The Role Of Malnutrition On Outcomes Of Multisystem Inflamma...mentioning
confidence: 99%